Prosodic Phrasing of Good Speakers in English and Czech - Skarnitzl, Radek; Hledíková, Hana (Frontiers in Psychology, 2022)
Prosodic patterning is known to affect the impression that speakers make on their listeners. This study explores prosodic phrasing in good public speakers of American English and Czech. Czech is a West Slavic language whose intonation is reported to be flatter and prosodic phrases longer than in English. We analyzed prosodic characteristics of 10 speakers of Czech and American English who appeared in TEDTalks, assuming such appearance to be a mark of a “good speaker”. Our objective was to see whether prosodic phrasing will be more similar in these public speeches between the two languages. We measured the length of prosodic phrases, speech rate in each phrase, and pitch range and melodic variability in the entire phrase, as well as in its pre-nuclear and nuclear portion. The number of syllables per phrase was higher in Czech than in English, although phrases were generally very short in both languages. The melodic indicators confirm smaller melodic variability in Czech even in publicly performed TEDTalks. Overall, our results show that there are differences between Czech and English prosodic phrasing in good public speakers, but that the genre also affects phrasing. Prosodic rendition – especially prosodic phrase length and melodic variability – is therefore a vital, albeit somewhat language-specific aspect of speech performance which public speakers should pay close attention to, both in their native language and in foreign languages.